2014
DOI: 10.1038/cddis.2014.329
|View full text |Cite
|
Sign up to set email alerts
|

FAK competes for Src to promote migration against invasion in melanoma cells

Abstract: Melanoma is one of the most deadly cancers because of its high propensity to metastasis, a process that requires migration and invasion of tumor cells driven by the regulated formation of adhesives structures like focal adhesions (FAs) and invasive structures like invadopodia. FAK, the major kinase of FAs, has been implicated in many cellular processes, including migration and invasion. In this study, we investigated the role of FAK in the regulation of invasion. We report that suppression of FAK in B16F10 mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 54 publications
8
57
0
Order By: Relevance
“…It has been hypothesized that focal adhesions sequester Src to areas at the periphery of the cell, reducing the pool of Src kinase available to phosphorylate invadopodia components (Chan et al, 2009). A similar phenotype was observed in melanoma, where suppression of focal adhesions led to decreased migration, but increased invadopodia (Kolli-Bouhafs et al, 2014). We show that ADAM12 knockdown significantly inhibited focal adhesion turnover.…”
Section: Discussionsupporting
confidence: 54%
“…It has been hypothesized that focal adhesions sequester Src to areas at the periphery of the cell, reducing the pool of Src kinase available to phosphorylate invadopodia components (Chan et al, 2009). A similar phenotype was observed in melanoma, where suppression of focal adhesions led to decreased migration, but increased invadopodia (Kolli-Bouhafs et al, 2014). We show that ADAM12 knockdown significantly inhibited focal adhesion turnover.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, the results obtained from the FAK-heterozygous mice were phenocopied using FAK kinase inhibitors (44). In addition, other studies have shown that FAK kinase activity negatively regulates invadopodia activity, thus inhibition of FAK can actually increase invasion (45,46). Given this complicated role of FAK, it remains possible that inhibition of FAK kinase activity may provide an advantage for cancer cell survival and invasion, resulting in enhanced metastasis, as observed here.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cells that underwent EMT were shown to migrate less than pre-EMT cells, indicating that migration and invasion processes can be disjoined [44]. Kolli-Bouhafs and colleagues (2014) demonstrated that mutation on FAK kinase (Tyr397) induced decreased migration but increased invasive properties in B16F10 melanoma cells [47]. All these lead us to infer that increased invasion does not have to be accompanied by increased migration.…”
Section: Discussionmentioning
confidence: 99%